2021
DOI: 10.36452/jkdoktmeditek.v27i2.2022
|View full text |Cite
|
Sign up to set email alerts
|

Kajian Efektivitas Insektisida Berbahan Bunga Krisan (Chrysanthemum cinerariaefolium) dan Jeruk Nipis (Citrus aurantifolia) Terhadap Mortalitas Nyamuk

Abstract: Nyamuk merupakan salah satu vektor penyakit bagi manusia seperti Demam Berdarah Dengue (DBD), malaria, chikungunya, filariasis, dan sebagainya. Habitat tempat tinggal nyamuk ini erat hubungannya dengan lingkungan tempat tinggal manusia sehingga penularan sangat rawan terjadi. Upaya yang dilakukan untuk mengurangi insidensi tersebut salah satunya yaitu dengan penggunaan insektisida sintesis maupun bioinsektisida. Tinjauan pustaka ini ditulis dengan tujuan untuk mengetahui kajian efektivitas insektisida berbahan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…It is reported that after undergoing a three-hour maceration process, kaffir lime (Citrus hystrix DC) leaves yield 63.66% citronellal (25). Lime (Citrus aurantifolia) peel also contains citronellal which can be used as an ingredient in making insecticides (26). There are several chemical processes involving citronellal (27).…”
Section: Observation Timementioning
confidence: 99%
“…It is reported that after undergoing a three-hour maceration process, kaffir lime (Citrus hystrix DC) leaves yield 63.66% citronellal (25). Lime (Citrus aurantifolia) peel also contains citronellal which can be used as an ingredient in making insecticides (26). There are several chemical processes involving citronellal (27).…”
Section: Observation Timementioning
confidence: 99%